2023
DOI: 10.1002/jeq2.20426
|View full text |Cite
|
Sign up to set email alerts
|

Resolving new and old phosphorus source contributions to subsurface tile drainage with weighted regressions on discharge and season

Abstract: Agricultural losses of dissolved reactive phosphorus (DRP) emanate from both historic P applications (i.e., “old P”) and recently applied fertilizer (i.e., “new P”). Understanding the relative contributions of these sources is important for mitigating DRP losses from agriculture. This study provides a proof‐of‐concept for resolving new P vs. old P source contributions to DRP losses in subsurface tile drainage using edge‐of‐field water quality data and management records from eight fields in Ohio. Weighted regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
0
3
1
Order By: Relevance
“…This study is the first to estimate new P losses from tile drainage systems across a large number of fields and P applications. Average new DRP estimates from inorganic fertilizer applications (41 g P ha −1 ) were lower than an earlier analysis of a small subset of the same dataset (86 g P ha −1 ) (W. Osterholz, Shedekar, et al., 2023), likely due to the greater frequency of injected applications in the current study. A separate analysis of two fields included in this study indicated that inorganic fertilizer resulted in new DRP losses of 30 and 410 g P ha −1 (Williams et al., 2022), within the range found in this study.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…This study is the first to estimate new P losses from tile drainage systems across a large number of fields and P applications. Average new DRP estimates from inorganic fertilizer applications (41 g P ha −1 ) were lower than an earlier analysis of a small subset of the same dataset (86 g P ha −1 ) (W. Osterholz, Shedekar, et al., 2023), likely due to the greater frequency of injected applications in the current study. A separate analysis of two fields included in this study indicated that inorganic fertilizer resulted in new DRP losses of 30 and 410 g P ha −1 (Williams et al., 2022), within the range found in this study.…”
Section: Discussioncontrasting
confidence: 77%
“…Daily water quality data were analyzed with the weighted regressions on discharge and season (WRDS) method, with new P loss risk windows used to define P loss periods and resolve the contributions of new and old sources (W. Osterholz, Shedekar, et al., 2023). The WRDS models are a modified version of the WRTDS model (Hirsch et al., 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently have P inputs and outputs in these basins aligned (Powers et al., 2016); however, water quality remediation faces unprecedented challenges from legacy P (Sharpley et al., 2013). Legacy soil P has been estimated to account for >80% of dissolved reactive phosphorus (DRP) loss from tile‐drained agricultural fields in the US Midwest (Osterholz et al., 2023) and often results in chemostatic transport behavior at both field (Guan et al., 2011; Williams et al., 2018) and watershed scales (Basu et al., 2010; Jawitz & Mitchell, 2011; King et al., 2017). As a result, legacy soil P can mask the effect of conservation on downstream water quality (Meals et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing P and K inputs is a critical component of increasing profitability for grain producers. Sufficient P and K fertilizer must be supplied to meet crop demand (Bender et al., 2013, 2015; Woli et al., 2017), but indiscriminate fertilizer application can result in loss of applied nutrients (Guo et al., 2021; Kast et al., 2021; King et al., 2015), and excessive soil test values can result in higher nutrient losses (Osterholz et al., 2020, 2022), resulting in subsequent water quality declines. Finding a balance between agronomic nutrient needs and environmental outcomes is conceptually straightforward but much more difficult in practice due to the complex nature of agroecosystems (Withers et al., 2019).…”
Section: Introductionmentioning
confidence: 99%